1976
DOI: 10.1113/expphysiol.1976.sp002366
|View full text |Cite
|
Sign up to set email alerts
|

The Projection of the Retina, Including the ‘Red Area’, on to the Optic Tectum of the Pigeon

Abstract: The optic tectum of the pigeon has been mapped physiologically, including much of the inferior surface. There are two separate regions of high magnification factor, the projection areas of the fovea and the middle of the red area in the retina, each of which has a correspondingly high density of neurones in the ganglion cell layer.Many avian retinae differ from those of mammals in that they contain two regions of increased ganglion cell density instead of one. In hawks there are two foveae: one central looking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(46 citation statements)
references
References 19 publications
3
42
1
Order By: Relevance
“…Retinal ganglion cells project [directly and/or indirectly (Uchiyama & Watanabe, 1985;Woodson et al, 1991)] onto the neurons of origin of the tecto-ION projection, which in turn project onto the isthmo-optic neurons. At each of these stages, topography is respected approximately and the predominant influence is excitatory (Clarke & Whitteridge, 1976;Uchiyama, 1989). The ION neurons innervate amacrine cells in the ventral retina, their most powerful input being via pericellular nests onto association amacrines that we identify as type II proprioretinal cells (Catsicas et al, 1987a).…”
Section: A Proposed Circuit For Attentional Switchingmentioning
confidence: 99%
“…Retinal ganglion cells project [directly and/or indirectly (Uchiyama & Watanabe, 1985;Woodson et al, 1991)] onto the neurons of origin of the tecto-ION projection, which in turn project onto the isthmo-optic neurons. At each of these stages, topography is respected approximately and the predominant influence is excitatory (Clarke & Whitteridge, 1976;Uchiyama, 1989). The ION neurons innervate amacrine cells in the ventral retina, their most powerful input being via pericellular nests onto association amacrines that we identify as type II proprioretinal cells (Catsicas et al, 1987a).…”
Section: A Proposed Circuit For Attentional Switchingmentioning
confidence: 99%
“…Because SLu neurons have RFs twice as large as Ipc neurons (45 Ϯ 15 deg in diameter vs 20 Ϯ 3 deg), feedback from the SLu would affect a larger tectal area than feedback from the Ipc. Thus, a 1 deg visual spot activating a tectal area of 0.1 mm in diameter (Clarke and Whitteridge, 1976) would elicit simultaneous feedback from the SLu and Ipc encompassing a tectal area of ϳ4.5 and 2 mm in diameter, respectively, both larger than the retinal input in the superficial layers. For visual stimuli moving in one direction, feedback from the Ipc and SLu may exert a priming effect on neurons ahead of the visual wave-front propagating across the tectal surface, e.g., by targeting the shepherd-crook neurons projecting back to the isthmi or the widely distributed bottlebrush endings of tectal ganglion cells.…”
Section: Synchronized Feedback To the Teo From The Ipc And Slumentioning
confidence: 99%
“…Neuroanatomical [Hamdi and Whitteridge, 1954;McGill et al, 1966;Hard, 1972;Hunt and Webster, 1975;Remy and Güntürkün, 1991] and electrophysiological [Hamdi and Whitteridge, 1954;Bilge, 1971;Clarke and Whitteridge, 1976] studies have shown that the avian retina primarily projects onto the contralateral tectum in a topographical manner. The dorsal and ventral retina project onto the ventral and dorsal tectum, respectively; and the horizontal meridian of the retina is represented in the lateral tectum.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical and electrophysiological mappings [Bilge, 1971;Clarke and Whitteridge, 1976;Remy and Güntürkün, 1991;Karten et al, 1997] have indicated that the ventral tectum is the projection region of the dorsal retina with the red field, which corresponds to the pecking field in pigeons [Goodale, 1983;Nalbach et al, 1990]. The isthmo-optic nucleus, a major component of the centrifugal system in birds, mainly receives input from the ventral tectum [Woodson et al, 1995].…”
Section: Introductionmentioning
confidence: 99%